2023
DOI: 10.1021/acsami.3c10085
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitride Grafting Modification of Poly(lactic acid) to Maximize UV Protection and Mechanical Properties for Packaging Applications

Maofan Zhou,
Gengping Wan,
Guizhen Wang
et al.

Abstract: Due to their biobased nature and biodegradability, poly­(lactic acid) (PLA) rich blends are promising for processing in the packaging industry. However, pure PLA is brittle and UV transparent, which limits its application, so the exploration of nanocomposites with improved interfacial interactions and UV absorbing properties is worthwhile. We therefore developed and optimized synthesis routes for well-designed nanocomposites based on a PLA matrix and graphitic carbon nitride (g-C3N4; CN) nanofillers. To enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The introduction of filler thus clearly induces a ductile-brittle transition. Similarly, Zheng et al [20] reported an increase in tensile modulus and a significant decrease in elongation at break where HDPE was reinforced with 3 wt% of EG. Furthermore, the results are in line with the results found by Liu et al [55], as their results indicated a strong improvement in elastic modulus through the addition of 1 wt% of GO in a polyimide matrix.…”
Section: Mechanical and Tribological Characterisation In View Of Dura...mentioning
confidence: 82%
See 2 more Smart Citations
“…The introduction of filler thus clearly induces a ductile-brittle transition. Similarly, Zheng et al [20] reported an increase in tensile modulus and a significant decrease in elongation at break where HDPE was reinforced with 3 wt% of EG. Furthermore, the results are in line with the results found by Liu et al [55], as their results indicated a strong improvement in elastic modulus through the addition of 1 wt% of GO in a polyimide matrix.…”
Section: Mechanical and Tribological Characterisation In View Of Dura...mentioning
confidence: 82%
“…It further follows from Figure 6c the virgin polymer materials showed strain hardening near the end of the tensile te with PA11 also showing some signs of necking. The composites, on the other hand, not show this ductile behaviour, as fillers within the polymer matrix acted as stress c centrators, therefore raising the localized stresses before failure occurred [20]. The in duction of filler thus clearly induces a ductile-brittle transition.…”
Section: Mechanical and Tribological Characterisation In View Of Dura...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials bring the highest specific surface area, and thus often an enhanced chemical reactivity. [3][4][5][6][7] Moreover, they often exhibit improved mechanical strength, hardness, and toughness compared to their bulk counterparts because the small size generally allows for better control over the arrangement of atoms and thus the creation of stronger bonds. [8][9][10] Examples are (semi-)metal oxides, active carbon, porous polymers, zeolites, and metal-organic frameworks (MOFs).…”
Section: Introductionmentioning
confidence: 99%